Dragon's tail : the lucky country after the China boom - Charlton, Andrew (Quarterly Essay., 2014)
In Dragon's Tail, Andrew Charlton explores the supercharged rise of China and considers Australia's future as the Chinese dragon stirs and shifts. China's rise has been perhaps the most significant economic event in two centuries, occurring 100 times more quickly and on a scale 1000 times larger than Britain's Industrial Revolution. Since 2000, Australia has been an essential part of this transformation, providing the raw materials to feed China's frantic manufacture of steel vertebrae for everything from cars and trucks to railways, apartments and office towers. China's appetite for resources.